Learning the hard way - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
New ways of developing agricultural technologies: the Zanzibar experience with participatory Integrated Pest Management By G C A Bruin & F Meerman, co-publication Wageningen University and Research Centre and CTA. 2001. 167 pp. ISBN 90 6754 624 0 CTA n